Penguatan Posyandu Remaja Menuju Generasi Sehat Di Dusun 3 Desa E Wonokerto Kecamatan Tugumulyo Kabupatan Musi Rawas - Pipit Meilasari; Sudayati, Any; Js , Dewi Susanti; Wulandari4, Wulandari (Utami Publisher, 2025)
This community service program aims to increase awareness and participation among adolescents in maintaining health through the establishment and strengthening of Posyandu Remaja (Youth Integrated Health Post) in Wonokerto Village, Tugumulyo Sub-district, Musi Rawas Regency. The main issues identified include the low level of adolescent knowledge regarding physical and mental health, limited access to youth-friendly reproductive health information, and the absence of a specific platform that actively involves adolescents in promotive and preventive health efforts. The activities were conducted from June 3 to June 14, 2025, through several stages including socialization, education, training, and evaluation. The implementation method employed participatory and educational approaches, involving adolescents as both subjects and partners of the program. The results showed a significant increase in adolescents' understanding of relevant health issues, the formation of a youth communication forum. This activity had a positive impact on strengthening adolescent capacity in adopting healthy behaviors and reinforcing community-based health services at the village level. Recommendations from this program include the importance of ongoing mentoring for youth cadres, integrating the youth health post into the village program, and replicating this model in other villages within Musi Rawas Regency